Implementation of Optical Character Recognition Using Raspberry Pi for Visually Challenged Person - Thiyagarajan, S; G.Saravana Kumar, Dr; Praveen Kumar, E; Sakana, G (International Journal of Engineering and Technology, 2018)
Blind people are unable to perform visual tasks. The majority of published printed works does not include Braille or audio versions, and digital versions are still a minority. In this project, the technology of optical character recognition (OCR) enables the recognition of texts from image data. The system is constituted by the raspberry pi, HD camera and Bluetooth headset. This technology has been widely used in scanned or photographed documents, converting them into electronic copies. The technology of speech synthesis (TTS) enables a text in digital format to be synthesized into human voice and played through an audio system. The objective of the TTS is the automatic conversion of sentences, without restrictions, into spoken discourse in a natural language, resembling the spoken form of the same text, by a native speaker of the language.Â Â